Design of Allosteric Stimulators of the Hsp90 ATPase as New Anticancer Leads. Issue 22 (22nd March 2017) - D'Annessa, Ilda; Sattin, Sara; Tao, Jiahui; Pennati, Marzia; Sànchez‐Martìn, Carlos; Moroni, Elisabetta; Rasola, Andrea; Zaffaroni, Nadia; Agard, David A.; Bernardi, Anna; Colombo, Giorgio
Abstract: Allosteric compounds that stimulate Hsp90 adenosine triphosphatase (ATPase) activity were rationally designed, showing anticancer potencies in the low micromolar to nanomolar range. In parallel, the mode of action of these compounds was clarified and a quantitative model that links the dynamic ligand–protein cross‐talk to observed cellular and in vitro activities was developed. The results support the potential of using dynamics‐based approaches to develop original mechanism‐based cancer therapeutics. Abstract : Perturbation of Hsp90 kinetics : Development of quantitative structure–dynamics–activity relationships facilitates the rational design of allosteric stimulators of the adenosine triphosphatase (ATPase) activity of the molecular chaperone Hsp90. The compounds modulate the functional cycle of the chaperone and represent promising anticancer drugs.